The Transition on the small screen and its impact on the collective imagination: Gender representation in Verano azul - Zapatero Flórez, Cristina (Historia y Comunicación Social, 2022)
Even though Verano azul is one of the most emblematic Spanish Television (TVE) series of the Transition, its impact on the collective imagination has not been mirrored in the academic field. This research approaches the gender representation in Mercero’s series through a content analysis methodology, in order to uncover how the spirit of the times of the Transition was forged in the fiction of the small screen. The findings show that Verano azul features a wide range of new masculinities, with no real correlate in the construction of new femininities. The series also includes new themes and values, defended or at least put forward by its protagonists, which reflect the historical change they are experiencing.